The Use of Edmodo Media in Islamic Religious Education Learning to Increase Learning Motivation of Class XII Science Students of SMAN 3 Mamuju - Wardiah Wardiah (CV. Rayyan Dwi Bharata, 2023)
This thesis discusses the use of edmodo media in learning Islamic Religious Education in increasing the learning motivation of class XII science students of SMA Negeri 3 Mamuju, The objectives of this study are (1) To find out how the use of edmodo media in learning Islamic Religious Education in class XII science students at SMA Negeri 3 Mamuju. (2) To find out how the level of learning motivation of class XII science students in Islamic Religious Education Learning at SMA Negeri 3 Mamuju (3) Shows that the use of edmodo media in PAI learning can increase the learning motivation of class XII science students at SMA Negeri 3 Mamuju.This research uses a quantitative approach, the type of research is quasi-experimental design research (pseudo-experiment). The population in this study was all class XII science students totaling 60 people. In sampling, the Cluster Random Sampling technique is used, with class XII IPA 1 as the experimental class and class XII IPA 2 as the control class. The research instrument is observation with data collection techniques, observing student activities during learning, providing tests, questionnaires before and after learning to measure student learning motivation, and documentation. The results of this study show that : (1) The use of edmodo media in learning Islamic Religious Education can increase learning motivation in students of grade XII Science SMA Negeri 3 Mamuju. This is evident from the Independent Samples T Test (T test) questionnaire data after learning with edmodo media was applied. the result obtained is Sig (2-tailed) = 0.040 2 α (0.1) then H0 is rejected and H1 is accepted. (2) Based on questionnaire data tests and observations conducted by researchers, it was found that the level of student motivation was very high in the experimental class after being given treatment than in the control class. As for the results of the data obtained Sig (2-tailed) = 0.040 2 α (0.10), H0 failed to be rejected and H1 was accepted.